Labtablet: multi domain laboratory notebook - Ricardo Filipe Carvalho Amorim (2014)
The researching process can sometimes generate a lot of information that is then used to support a thesis or conclusion. The process of gathering such information is currently based on paper notebooks or basic tools which leads in many of the cases to the loss of documents when the work is terminated and thus loosing the connection between the thesis and the data that supports it.LabTablet aims to explore the available tools and create an application to make the process of storing those documents automatic and transparent to the user and independent of his/her area of research.